Somatic mutations in the p53 tumor suppressor gene in rheumatoid arthritis synovium - Firestein, Gary S. (The National Academy of Sciences of the USA, 1997)
The factors that regulate the perpetuation and invasiveness of rheumatoid synovitis have been the subject of considerable inquiry, and the possibility that nonimmunologic defects can contribute to the disease has not been rigorously addressed. Using a mismatch detection system, we report that synovial tissue from the joints of severe chronic rheumatoid arthritis patients contain mutant p53 transcripts, which were not found in skin samples from the same patients or in joints of patients with osteoarthritis. Mutant p53 transcripts also were identified in synoviocytes cultured from rheumatoid joints. The predicted amino acid substitutions in p53 were identical or similar to those commonly observed in a variety of tumors and might influence growth and survival of rheumatoid synoviocytes. Thus, mutations in p53 and subsequent selection of the mutant cells may occur in the joints of patients as a consequence of inflammation and contribute to the pathogenesis of the disease.